Some data about seaweeds in littoral zone of Nghe An and Ha Tinh provinces - Chung, Mai Van; Dien, Nguyen Duc (Academia Journal of Biology, 2014)
In Vietnam, seaweeds occupied in most of lagoons, estuaries, bays and territorial waters. Many researches have been carried out to estimate their composition, distribution in sea regions. This article presents some data about seaweeds in the littoral zones of Nghean and Hatinh provinces. A total of 42 seaweed species were found in this zone. They belonged to 25 genera, 17 families, 12 orders, 5 classes and 3 divisions (Chlorophyta, Phaeophyta and Rhodophyta). Among them, 30 species are new for this area. There are 31 species mainly distributed in medial belt besides 1 species found in high belt and 10 species lived on seabed in low belt. The quantities of seaweed species and multi-species genera in the Nghean province are more abundant than in the Hatinh province. That are the most difference of the composition and distribution of seaweeds in littoral zone in these provinces.